Advancements in mesenchymal stem cell therapy for chronic wounds: challenges, innovations, and future directions - Tang, Yi; Su, Tong; Huang, Baochuan; Xu, Qihong; Chen, Qingjiang; Zhang, Saiqiong; Li, Wuquan (Frontiers in Cell and Developmental Biology, 2026)
The management of chronic wounds remains challenging due to their complex pathophysiology, poor response to conventional therapies, and significant impact on patients’ quality of life. mesenchymal stem cells (MSCs) have garnered attention as a potential treatment due to their regenerative and immunomodulatory properties. This review summarizes preclinical and clinical advancements in MSC-based therapies for chronic wound healing. MSCs promote tissue regeneration through various mechanisms, including differentiation into skin cell lineages, modulation of inflammation, angiogenesis, and paracrine release of bioactive factors. Current research focuses on identifying viable MSC sources, optimizing delivery methods, and understanding their mechanisms for clinical use. Despite progress, challenges remain, including inconsistent results, poor MSC survival in the wound microenvironment, and variability in regenerative capacity across MSC sources. Future research should focus on developing standardized guidelines for MSC preparation and conducting long-term randomized trials to assess safety, efficacy, and potential risks. In conclusion, this review highlights current evidence and identifies key challenges for the clinical application of MSCs in chronic wound healing.